X-ray examination of bone density in allograft-prosthesis composite (іn vivo experiment) - Vyrva, Oleg; Golovina, Yanina; Malyk, Roman; Karpinsky, Mykhaylo; Karpinska, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective. To determine the most effective method of segmental bone allograft fixation during allograft — prosthesis composite based on searching the x-ray density of bone tissue at experimental animals. Methods. The work was performed on 28 laboratory white male rats (age 5 months, weight 350–400 g), which were divided into 2 groups, 14 animals in each group. All animals underwent allograft-prosthesis composite hip replacement: after transverse osteotomy of the femur in the 1st group of animals, after step cut osteotomy in the 2nd group. Animals were withdrawn from the experiment after 3 and 6 months after operation. The optical bone regenerate density in the contact of allograft and the recipient’s bone areas and the cortical layer of the recipient’s bone below the distal end of endoprosthesis were measured on Х-ray images. Results. Optical bone regenerate density after 3 and 6 months after operation had significant difference between recipient’s bone in both groups (p < 0.05). There was no statistically significant difference (р = 0.373) of recipient’s bone density depending on using different osteotomy types on the cutoff date of the study (6 months). But bone regenerate got more density after step-cut osteotomy ((216 ± 26) units) which was significantly (p = 0.001) compare to transverse osteotomy ((161 ± 19) units). Conclusions. The using of long bone allograft-prosthesis composite with implementation a step cut osteotomy contributes to the most rapid increase in bone regenerate density than transverse osteotomy. This is due to the achievement of better stability during fixation of the bone allograft and the bone of the recipient due to the step cut osteotomy, which contributes to fast regenerative process.